2016
DOI: 10.1007/s10877-016-9892-y
|View full text |Cite
|
Sign up to set email alerts
|

Design and validation of a questionnaire to evaluate the usability of computerized critical care information systems

Abstract: The implementation of computerized critical care information systems (CCIS) can improve the quality of clinical care and staff satisfaction, but also holds risks of disrupting the workflow with consecutive negative impacts. The usability of CCIS is one of the key factors determining their benefits and weaknesses. However, no tailored instrument exists to measure the usability of such systems. Therefore, the aim of this study was to design and validate a questionnaire that measures the usability of CCIS. Follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Validity of the rating models is based on content validity (structured development of the models following a holistic approach) as well as previously published analyses of criterion validity (conformity between different rating models with multiple correlation coefficients !0.8) and construct validity (intercorrelation analysis of the elements of the model rating the technical usability characteristics). 33 The reliability of the rating models has been demonstrated in a previously published analysis of the internal consistency and was shown to have Cronbach's a values of ! 0.93.…”
Section: The Questionnaire To Evaluate Ccis Usabilitymentioning
confidence: 97%
See 4 more Smart Citations
“…Validity of the rating models is based on content validity (structured development of the models following a holistic approach) as well as previously published analyses of criterion validity (conformity between different rating models with multiple correlation coefficients !0.8) and construct validity (intercorrelation analysis of the elements of the model rating the technical usability characteristics). 33 The reliability of the rating models has been demonstrated in a previously published analysis of the internal consistency and was shown to have Cronbach's a values of ! 0.93.…”
Section: The Questionnaire To Evaluate Ccis Usabilitymentioning
confidence: 97%
“…Extensive validation has shown that the questionnaire actually measures the usability of CCIS. 33 Because the questionnaire co-registers the known confounders of subjective usability ratings and their influences are included in our analyses, our results should be robust. However, a questionnaire study cannot achieve the level of internal validity that individual user interviews, observed user tests, or expert testing could achieve for usability assessment.…”
Section: Limitationsmentioning
confidence: 97%
See 3 more Smart Citations